Physiological responses of maize and cowpea to intercropping - Lima Filho, José Moacir Pinheiro (Pesquisa Agropecuaria Brasileira, 2000)
The effect of intercropping on plant water status, gas exchange and productivity of maize (Zea mays L.) cv. Centralmex, and cowpea (Vigna unguiculata L. (Walp)) cv. Pitiuba were evaluated under semi-arid conditions at the Embrapa-Centro de Pesquisa Agropecuária do Trópico Semi-Árido (CPATSA) at Petrolina, PE, Brazil. The treatments were: maize and cowpea as sole crops, at a population of 40,000 plants ha-1, and intercropped at a population of 20,000 plants ha-1. The results obtained in this paper appear to be related to the degree of competition experienced by the components, mainly for water and light. Maize intercropped had higher values of leaf water potential, stomatal conductance, transpiration and photosynthesis than as sole crop. Intercropped cowpea had higher values of leaf water potential but lower stomatal conductance, transpiration and photosynthesis than sole cowpea. Maize productivity increased 18% in relation to sole crop whereas a 5% decrease was observed with cowpea. Despite these facts the Land Equivalent Ratio obtained was 1.13 indicating intercropping advantage over the sole system. The higher partial Land Equivalent Ratio observed for maize suggests that this specie was the main component influencing the final productivity of the intercropping system studied.